CRISPR-Mediated Gene Editing to Assess the Roles of Tet2 and Dnmt3a in Clonal Hematopoiesis and Cardiovascular Disease. Issue 3 (20th July 2018) - Sano, Soichi; Oshima, Kosei; Wang, Ying; Katanasaka, Yasufumi; Sano, Miho; Walsh, Kenneth
Abstract : Rationale: : Clonal hematopoiesis has been associated with increased mortality and cardiovascular disease. This condition can arise from somatic mutations in preleukemic driver genes within hematopoietic stem/progenitor cells. Approximately 40 candidate driver genes have been identified, but mutations in only 1 of these genes, TET2 (ten-eleven translocation-2), has been shown to casually contribute to cardiovascular disease in murine models. Objective: : To develop a facile system to evaluate the disease characteristics of different clonal hematopoiesis driver genes using lentivirus vector and CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/clustered regularly interspaced short palindromic repeat–associated 9) methodology. Using this methodology, evaluate whether Dnmt3a (DNA [cytosine-5]-methyltransferase 3a)—a commonly occurring clonal hematopoiesis driver gene—causally contributes to cardiovascular disease. Methods and Results: : Lentivirus vectors were used to deliver Cas9 and guide RNA to introduce inactivating mutations in Tet2 and Dnmt3a in lineage-negative bone marrow cells. After implantation into lethally irradiated mice, these cells were engrafted and gave rise to labeled blood cell progeny. When challenged with an infusion of Ang II (angiotensin II), mice with inactivating mutations in Tet2 or Dnmt3a displayed greater cardiac hypertrophy, diminished cardiac function, and greater cardiac and renal fibrosis. In comparison with Tet2, inactivation of Dnmt3a did not lead to detectable expansion of the mutant hematopoietic cells during the time course of these experiments. Tet2 inactivation promoted the expression of IL (interleukin) 1β, IL-6, and Ccl5, whereas Dnmt3a inactivation promoted the expression of Cxcl1 (CXC chemokine ligand), Cxcl2, IL-6, and Ccl5 in a lipopolysaccharide-stimulated macrophage cell line. Conclusions: : Experiments using lentivirus vector/CRISPR methodology provided evidence suggesting that inactivating DNMT3A mutations in hematopoietic cells contributes to cardiovascular disease. Comparative analyses showed that inactivation of Tet2 and Dnmt3 was similar in their ability to promote Ang II-induced cardiac dysfunction and renal fibrosis in mice. However, gene-specific actions were indicated by differences in kinetics of hematopoietic stem/progenitor cell expansion and different patterns of inflammatory gene expression. Abstract : Supplemental Digital Content is available in the text.